Students and Online Learning: Friends or Foes? - Nine Febrie Novitasari (Ethical Lingua: Journal of Language Teaching and Literature, 2021)
The Covid-19 pandemic has transformed the system of education in Indonesia. The pandemic due to the corona virus has made the Indonesian government alter the education system from conventional meeting to online meeting. However, the closure of schools in Indonesia during the pandemic has ignited problems for teachers, students, and parents. Despite the benefits it offers, online learning also has some evident drawbacks. The pros and cons of online learning are also experienced by the students at UNARS. Accordingly, an online survey was conducted among the students to see how they perceived online learning. The result of the survey shows that although not as pleasant as offline meeting, online meeting is rated somewhat enjoyable by 50,8% of the students.